Eigencolor radiochromic film dosimetry. Issue 5 (1st April 2021) - Bouchard, Hugo; Billas, Ilias; Subiel, Anna; Duane, Simon
Abstract : Purpose: The goal of this work is to propose a new multichannel method correcting for systematic thickness disturbances and to evaluate its precision in relevant radiation dosimetry applications. Methods: The eigencolor ratio technique is introduced and theoretically developed to provide a method correcting for thickness disturbances. The method is applied to EBT3 Gafchromic TM film irradiated with cobalt‐60 and 6 MV photon beams and digitized with an Epson 10000XL photo scanner. Dose profiles and output factors of different field sizes are measured and analyzed. Variance analysis of the previous method of Bouchard et al. ["On the characterization and uncertainty analysis of radiochromic film dosimetry" Med Phys. 2009;36 :1931‐1946] is adapted to the new approach. Uncertainties are predicted for relevant applications. Results: Results show that systematic disturbances attributed to thickness variations are efficiently corrected. The method is shown efficient to identify and correct for dark spots which cause systematic errors in single‐channel distributions. Applications of the method in the context of relative dosimetry yields standard uncertainties ranging between 0.8% and 1.9%, depending on the region of interest (ROI) size and the film irradiation. Variance analysis predicts that uncertainty levels between 0.3% and 0.6% are achievable with repeated measurements. Uncertainties are found to vary with absorbed dose and ROI size. Conclusions: The proposed multichannel method is efficient for accurate dosimetry, reaching uncertainty levels comparable to previous publications with EBT film. The method is also promising for applications beyond clinical QA, such as machine characterization and other advanced dosimetry applications.